Microphone based on Polyvinylidene Fluoride (PVDF) micro-pillars and patterned electrodes - Xu, J.; Dapino, M.J.; Gallego-Perez, D.; Hansford, D. (Sensors and actuators. A. Physical., 2009)
This article is focused on the development of an acoustic pressure sensor with extremely high sensitivity and small footprint. We propose a sensor design consisting of micron-sized Polyvinylidene Fluoride (PVDF) pillars which generate a charge when subjected to normal stresses associated with acoustic waves. A rigid membrane placed between the micro-pillars and the acoustic medium ensures high mechanical coupling. The electrode covering the micro-pillars is patterned to decrease the capacitance, and hence increase the sensitivity of the sensor. The key sensor parameters (diameter and height of the micro-pillars, gap between pillar edges, and number of pillars) are determined through a constrained optimization algorithm in which the penalty function is the sensor footprint. The algorithm incorporates the effects of mechanical and electrical properties of the sensor and conditioning amplifier. Details of the fabrication process are described. Nano-indentation tests demonstrate that the PVDF micro-pillar sensor exhibits piezoelectric responses under an applied voltage or strain, thus demonstrating the sensor concept.